A device capable of customizing nonlinear forces for vibration energy harvesting, vibration isolation, and nonlinear energy sink. (15th January 2021) - Zou, Donglin; Liu, Gaoyu; Rao, Zhushi; Tan, Ting; Zhang, Wenming; Liao, Wei-Hsin
Highlights: Continuous but not necessarily smooth nonlinear forces can be customized. The device is simple and does not need a complicated auxiliary structure. The device has no high requirements for the selection of spring parameters. Abstract: Nonlinear forces obtained via springs, magnets, buckling beams, etc., have been widely introduced into vibration energy harvesting, vibration isolation and nonlinear energy sink to improve performance. Although obtaining customized nonlinear forces as desired is difficult, it is quite useful to improve the dynamic performance. Therefore, a device capable of customizing nonlinear forces is developed in this study. The device consists of a pre-compressed spring, a bearing and a raceway, which are designed according to the nonlinear forces to be customized. It is assumed that the nonlinear forces to be customized are continuous (not necessarily smooth). As examples, a hardening nonlinear system, a softening nonlinear system, a bistable system, a tri-stable system, and a piecewise nonlinear system are customized in this study. Simulations and experiments prove its feasibility. The device enables designers to obtain the most suitable nonlinear forces for the dynamic systems. It can be easily applied to energy harvesting, vibration isolation, and nonlinear energy sink, etc.